71.1k views
4 votes
Z=a/b+c/d solve for A

User Drastega
by
5.1k points

1 Answer

6 votes

Answer:
a=(b(zd-c))/(d)

Explanation:

Having the following equation given in the exercise:


z=(a)/(b)+(c)/(d)

You can solve for "a" following this procedure:

1. You can apply the Subtraction property of equality and subtract
(c)/(d) from both sides of the equation:


z-((c)/(d))=(a)/(b)+(c)/(d)-((c)/(d))\\\\z-(c)/(d)=(a)/(b)

2. Now you must subtract the terms on the left side of the equation. Notice that the Least Common Denominator is "d". Then:


(zd-c)/(d)=(a)/(b)

3. Finally, you can apply the Multiplication property of equality and multiply both sides of the equation by "b". So, you get:


(b)((zd-c)/(d))=((a)/(b))(b)\\\\a=(b(zd-c))/(d)

User Karo
by
4.7k points